ANALISIS YURIDIS PERSEKONGKOLAN TENDER (STUDI PUTUSAN KPPU NOMOR 30/KPPU-I/2019) - Tsaliza Soraya Majid; N.G.N Renti Maharaini (Faculty of Law, Universitas Trisakti, 2023)
This journal examines the extent to which the sanctions imposed by the KPPU in its Decision No. 30/KPPU-I/2019 are in line with Law No. 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition, as well as the Regulation of the Goods/Services Procurement Policy Institution No. 12 of 2021 amending Presidential Regulation No. 16 of 2018 on Government Goods and Services Procurement. It also explores whether businesses are allowed to use another company's identity in the tender process. Based on research conducted using the Competition Law, Article 22 Guidelines, and relevant regulations, collusion is identified both horizontally and vertically, so in this case PT Hapsari Nusantara Gemilang and PT Ikhlas Bangunan Sarana should be placed on a blacklist, and PT Cipta Aksara Perkasa should face administrative fines. Additionally, PT Alfa Adiel should receive sanctions for using another company's identity in the tender process, which undermines fair competition. It is recommended that businesses uphold good faith by adhering to existing regulations during the tender process